Immersive Anthropological Methodology towards Sustainable Ecotourism: A Case Study of Bali, Indonesia - Sonawane, Shilpa Vinod; Wijaya, I Nyoman Cahyadi (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: This research aims to investigate and implement an anthropological methodology for achieving sustainable eco-tourism in Bali, Indonesia. Research methods: This qualitative method used involves a thorough examination and comparison of diverse scholarly works, case studies, and relevant texts. The qualitative comparative analysis provides a robust framework for interpreting the complex interplay of ideas, perspectives, and contextual factors embedded in the literature building upon and expanding the understanding of the subject matter within the broader academic discourse. Results and discussion: The research underscores the critical issues of water supply, waste management, and infrastructure development in Bali. Sustainable solutions, including cultural inclusion, eco-friendly housing, and natural supplements, are proposed to alleviate these challenges. Implications: The results signify a crucial step towards fostering environmental conservation and responsible tourism practices in this popular destination.